Entrepreneurship through Digital Transformation and Social Changes - CULIC, Lorina; HOSU, Ioan; VOINA, Andreea Nicoleta (2022)
This volume, Entrepreneurship through Digital Transformation and Social Changes,represents the conference outcome and embodies the authors’ efforts delivered through36 articles, structured into four sections. The contributions blend in a diverse approachstemming not just from the variety of topics tackled, but also through the perspectives oftheoretical and empirical work, elaborated in English or Romanian, fitting both extensivepapers and extended abstracts thoroughly discussed in the panels and workshops of theconference.